2013
DOI: 10.4103/0189-6725.115033
|View full text |Cite
|
Sign up to set email alerts
|

Acute cholecystitis from typhic origin in children

Abstract: Typhoid acalculous cholecystitis is a frequent complication in children. Late presentation and diagnosis is associated with complications. Cholecystectomy in association with antibiotic is the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Actually, authors reported the blockage of the cystic duct by an enlarged lymph node in one patient only [ 20 ]. Similarly, in the study by Gnassingbé et al, including 6 children with gangrenous or perforated AAC, where the histological features of gallbladder were described, no distal extrinsic compression on the biliary duct was reported [ 21 ].…”
Section: Infectious Acute Acalculous Cholecystitis In Childrenmentioning
confidence: 94%
“…Actually, authors reported the blockage of the cystic duct by an enlarged lymph node in one patient only [ 20 ]. Similarly, in the study by Gnassingbé et al, including 6 children with gangrenous or perforated AAC, where the histological features of gallbladder were described, no distal extrinsic compression on the biliary duct was reported [ 21 ].…”
Section: Infectious Acute Acalculous Cholecystitis In Childrenmentioning
confidence: 94%
“…7,8 Sabe-se que a infeção por Salmonella tem várias complicações associadas, como desidratação e bacteriemia. 9 No entanto, a colecistite aguda alitiásica é uma compli- cação rara na infeção por Salmonella, com a generalidade dos casos publicados referindo-se à infeção pela Salmonella typhi, [10][11][12][13] com escassos casos relatados na infeção por Salmonella enteritidis.…”
Section: -4unclassified
“…reported and its pathogenesis is not clear. [5][6][7] It has been postulated that the streptococcus enters the gall bladder through the mucous mem brane of the stomach by way of lymphatic channel producing toxin and lymphocytic infiltration responsible for the lesion in the gallbladder as well in the liver. [8] Patients with acute cholecystitis due to scarlet fever usually present with fever, right upper abdominal pain, vomiting and jaundice.…”
Section: Case Reportmentioning
confidence: 99%